Kenny's outlines of criminal law / by J.W. Cecil Turner. - Turner, J. W. Cecil (James William Cecil) (Cambridge University Press, 2013)
First published in 1962, as the eighteenth edition of a 1902 original, this book formed part of an ongoing series of elementary legal guides. The text was not intended to be a work on criminal jurisprudence, but rather to assist students to such an understanding of the rules of criminal law as would enable them to form a clear idea of the practical task confronting the prosecution and defence in the trials of specific people. This book will be of value to anyone with an interest in law and legal history.